Antibacterial and Antibiofilm of Purified β-glucan from Saccharomyces cerevisiae against Wound Infections Causative Bacteria - Khadam, Alyaa A; Salman, Jehan AS. (Iraqi Journal of Science, 2024)
Twenty species were isolated from wounds’ swabs. The most common bacterial species were Pseudomonas aeruginosa (8), Staphylococcus aureus (5), Escherichia coli (5) and S. epidermidis (2). These isolates underwent tests for biofilm formation and susceptibility to ten different antibiotic discs. Most isolates exhibited resistance to amikacin, aztreonam, and carbenicillin. However, they showed some sensitivity to ciprofloxacin, norfloxacin and imipenem. This study found out that all isolates were different in biofilm formation (weak, moderate, strong), except two isolates of E. coli. The determination of β-glucan effects produced by S. cerevisiae against multi-antibiotic resistant wound infection bacteria, were conducted through the Minimum Inhibitory Concentration (MIC). The antibacterial activity of β-glucan against wound infection causative bacteria was evaluated using the (MIC) ranging from 6.25 to 400 mg/mL. The antibiofilm effects of purified β-glucan (at sub-MIC) demonstrated highest inhibition percentage (92%) for biofilm formation after 72 h against multidrug-resistant (MDR) P. aeruginosa (2), while P. aeruginosa (5) had the lowest (32%). β-glucan activity on biofilm degradation was detected in all isolates. The highest percentage of biofilm degradation was 90% for MDR P. aeruginosa (1).